2011
DOI: 10.1017/s1751731110001382
|View full text |Cite
|
Sign up to set email alerts
|

Coat colours in the Massese sheep breed are associated with mutations in the agouti signalling protein (ASIP) and melanocortin 1 receptor (MC1R) genes

Abstract: Massese is an Italian dairy sheep breed characterized by animals with black skin and horns and black or apparent grey hairs. Owing to the presence of these two coat colour types, this breed can be considered an interesting model to evaluate the effects of coat colour gene polymorphisms on this phenotypic trait. Two main loci have been already shown to affect coat colour in sheep: Agouti and Extension coding for the agouti signalling protein (ASIP) and melanocortin 1 receptor (MC1R) genes, respectively. The Ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 49 publications
(59 reference statements)
4
70
3
5
Order By: Relevance
“…Surprisingly, Peñagaricano et al (2012) did not identify a significant difference in the expression of ASIP for black or white skin samples. The results contrast with those of Norris and Whan (2008) and Fontanesi et al (2011), who indicated the duplication of the functional ASIP region as a cause of the white phenotype. The other conclusion of the research is that ovine MC1R was not expressed in spotted skin samples.…”
Section: High-throughput Genetic Techniquesnext-generation Sequencingcontrasting
confidence: 98%
“…Surprisingly, Peñagaricano et al (2012) did not identify a significant difference in the expression of ASIP for black or white skin samples. The results contrast with those of Norris and Whan (2008) and Fontanesi et al (2011), who indicated the duplication of the functional ASIP region as a cause of the white phenotype. The other conclusion of the research is that ovine MC1R was not expressed in spotted skin samples.…”
Section: High-throughput Genetic Techniquesnext-generation Sequencingcontrasting
confidence: 98%
“…Mutations in ASIP have also been shown to be responsible for the wild-/self-type coat pattern polymorphism in Soay sheep (Gratten et al, 2010). Also, the duplicated copy allele (s) in ASIP gene was found to be associated with grey coat colour (Fontanesi et al, 2011), which could explain the observation that coat-colour variation from grey to black/white spotted (non-white coat colour) was marginally explained by SNPs in and close to the ASIP gene. In addition, recessive genetic variants at the ASIP were found to be associated with reduced lifetime fitness in a wild population of Soay sheep (Gratten et al, 2012).…”
Section: Asip As a Candidate Gene For White Versus Non-whitementioning
confidence: 97%
“…The highest-ranked SNP (s66432.1; F ST ¼ 0.731), which showed a single and strong selection signal, was located at the position 67.95 Mb within the ASIP gene. In sheep, the duplicated ASIP allele (s) was (were) found to account for the white and black sheep (for example, Norris and Whan, 2008;Fontanesi et al, 2011), and ASIP displayed strong evidence for positive selection in a quite recent study across a worldwide collection of breeds (Kijas et al, 2012). A total of four genomic regions containing X9 consecutive significant average values o0.05 were identified to be under positive selection using the five-SNP sliding-window analysis (Table 2), whereas no region was observed with balancing selection.…”
Section: Snps and Genes Under Selectionmentioning
confidence: 99%
“…In recent years, advances in high-throughput genome scan technologies, particularly DNA hybridization on array platforms and next-generation sequencing methods, have allowed the identification of a large number of structural variants in multiple species. Although not as comprehensive as those for human, CNV maps have been produced in cattle (2,3), horse (4), sheep (5,6), pig (7), goat (8), duck (9), and chicken (10,11).…”
mentioning
confidence: 99%